Effects of dietary mannan oligosaccharides in early weaning diets on growth, survival, fatty acid composition and gut morphology of gilthead sea bream (Sparus aurata, L.) larvae. (25th March 2017) - Eryalçin, Kamil Mert; Torrecillas, Silvia; Caballero, Maria Jose; Hernandez‐Cruz, Carmen Maria; Sweetman, John; Izquierdo, Marisol
Abstract: Early weaning of marine fish larvae with dry diets delays gut maturation and reduces growth rates. In juvenile and adult forms of several marine fish species, inclusion of dietary mannan oligosaccharides (MOS) improves gut integrity and functionality, but the effects of MOS inclusion in gilthead sea bream ( Sparus aurata, L.) larval diets have not been addressed yet. Thus, this study assesses the effects of dietary MOS inclusion on survival, growth performance, gut morphology, feed acceptance and quality of gilthead sea bream larvae. For that purpose, 16 days post‐hatched gilthead sea bream larvae were fed four graded levels of MOS (Biomos ®, Alltech, Nicholasville, KY, USA) in weaning diets as follows: 0 g kg −1 MOS, 0.5 g kg −1 MOS, 1.5 g kg −1 MOS and 2 g kg −1 MOS. Dietary MOS did not affect feed acceptance in gilthead sea bream larvae ( P > 0.05). MOS supplementation was correlated in a dose‐dependent way with higher larval survival ( P = 0.026). After 15 days of feeding, dietary MOS increased whole larvae ( P < 0.01) arachidonic acid, eicosapentaenoic acid and docosahexaenoic acid. Gilthead sea bream larvae fed 2 g kg −1 MOS presented higher gut occupation with goblet cells after feeding compared with larvae fed the other dietary treatments. Overall, the results suggest that inclusion of MOS in early weaning diets for gilthead sea bream improves essential fatty acid utilization and may promote growth and final survival.